Effect of Using Porcelanite as Partial Replacement of Fine Aggregate on Roller Compacted Concrete with Different Curing Methods (Journal of Engineering, 2016)
Roller-Compacted Concrete is a no-slump concrete, with no reinforcing steel, no forms, no finishing and wet enough to support compaction by vibratory rollers. Due to the effect of curing on properties and durability of concrete, the main purpose of this research is to study the effect of various curing methods (air curing, 7 days water curing, and permanent water curing) and porcelanite (local material used as an Internal Curing agent) with different replacement percentages of fine aggregate (volumetric replacement) on some properties of Roller-Compacted Concrete and to explore the possibility of introducing practical Roller-Compacted Concrete for road pavement with minimum requirement of curing. Specimens were sawed from slabs of (380*380*100) mm for determination of Ultrasonic Pulse Velocity (UPV) and Voids volume. Results show that using (5) % porcelanite improved the results of  UPV and Voids volume of Roller-Compacted Concrete (with air curing) as compared with reference Roller-Compacted Concrete (with permanent water curing) by percentages ranging from(3.6 to 28.9)% and (-8 to -15.5)% respectively.